ASAS MONOGAMI TERBUKA DALAM PERUNDANG-UNDANGAN PERKAWINAN ISLAM DI INDONESIA - Sam’un, Sam’un (The Indonesian Journal of Islamic Family Law, 2015)
Abstract: The existence of the effort of the Islamic family law reform in a number of Muslim countries in the 20th century has resulted a number of Islamic law, which has been conceived and began to change, though many of the changes are not so radical. One of the changes is the emergence of the open principle of monogamous as manifested in Undang-Undang No. 1 year 1974 about marital contract. It is mentioned that the original principle of marriage is monogamous. However, in the next article, Undang-Undang about marital contract is likely to open a way for husband to do polygamy which is then called an open principle of monogamous. In fact, there is a similarity between understanding of classical jurisprudence and Undang-Undang of marital contract, it is allowing conducting polygamy. However, Undang-Undang of marital contract initiates that every husband who wants to be polygamous must gain the permission from religion court. This permission is the intersection between both since it is a manifestation of one of the conditions that must be met by a husband when he is about polygamy, which is fair to all wives. The purpose of all above considerations is indeed to minimize the chance of conducting polygamy that is in line with the purpose of the renewal of Islamic law itself, namely the improvement of the womanâs status.Abstrak: Adanya usaha pembaharuan Hukum Keluarga Islam di sejumlah negara Muslim pada abad ke-20 ini mengakibatkan sejumlah pokok-pokok Hukum Islam yang selama ini dipahami, mulai mengalami perubahan, meskipun banyak dari perubahan tersebut tidak begitu radikal (mendasar). Salah satu perubahannya adalah munculnya asas monogami terbuka dalam perundang-undangan perkawinan di Indonesia. Undang-undang No.1 Tahun 1974 Tentang Perkawinan menyebutkan, bahwa asas perkawinan itu monogami. Akan tetapi, pada pasal selanjutnya, UU Perkawinan tersebut masih membuka jalan bagi para suami yang ingin berpoligami. Inilah yang dinamakan asas monogami terbuka. Pada dasarnya, pemahaman dalam fikih klasik dan pemahaman dalam UU Perkawinan tidaklah berbeda, yakni sama-sama membolehkan poligami. Hanya saja, UU Perkawinan berinisiatif agar setiap suami yang hendak berpoligami, harus melalui izin pengadilan. Izin pengadilan inilah yang menjadi titik temu antara UU perkawinan dan fikih klasik, karena dalam izin pengadilan mangandung manifestasi salah satu syarat yang harus dipenuhi oleh suami tatkala hendak berpoligami, yakni adil terhadap semua istri. Tujuan daripada semua ketentuan tersebut adalah mempersempit peluang terjadinya poligami sehingga berbanding lurus dengan tujuan pembaharuan Hukum Islam itu sendiri, yakni peningkatan status wanita di abad ini.Kata Kunci : Asas Monogami, Perundang-undangan, Fikih Klasik